The Law of the Sea and PRC Gray-Zone Operations in the South China Sea. Issue 4 (October 2022) - McLaughlin, Rob
Abstract : A growing number of incidents—particularly since 2009—highlight the South China Sea (SCS) as the preeminent venue for the People's Republic of China (PRC) maritime gray zone operations. "Gray zone operations" are, in essence, operations that are designed to exploit or create legal (and other) uncertainties for a military or strategic advantage. A prominent example is the way that China has used the so-called nine(ten)-dash line without fully explaining the legal basis for it. There are other examples, as well. China has deliberately cultivated uncertainty about the sovereign status of maritime militia vessels—and thus about whether and how the conduct of these vessels might be directly attributable to the PRC. It has harassed U.S. survey vessels seventy-five nautical miles (nm) south of Hainan Island in an effort to disrupt military survey operations that it claims are impermissible and has sunk a Philippine fishing vessel at Reed Bank in an effort to enforce Chinese claims to exclusive fisheries rights in this area. It has also asserted claims and enforcement rights in zones that clearly belong to other states—including actions against Indonesian fishing vessels in seas in the vicinity of the Natuna Islands, which are part of the Indonesian Exclusive Economic Zone (EEZ) (and Continental Shelf). And it has conducted operations on the basis of inapplicable maritime zone rights, such as by asserting a territorial sea and thus the right to control innocent passage around low-tide elevations with artificial installations built upon them—such as with Mischief Reef. The list goes on.